Addressing Feeding Disorders Using High-Probability Sequencing for Children and Adolescents with Developmental Disabilities. (September 2019) - King, Seth; Johnson, Hayley E.; Burch, Taneal; Chitiyo, Argnue
Feeding disorders exhibited by children with developmental disabilities, which include limiting food intake or refusing to consume solid foods, often result in poor health consequences. Interventions for feeding disorders vary in terms of their acceptability to children with disabilities and their families. One specific procedure, the high-probability sequence, is a nonrestrictive approach where requests with which a child has a history of compliance are presented prior to requests associated with noncompliance. This article reviewed research concerning the application of high-probability sequencing for feeding disorders among children and adolescents with developmental disabilities. Experimental studies published between 1970 and 2018 in English as either peer-reviewed articles or dissertations were eligible for descriptive review. Identified articles ( N = 15) evaluated high-probability sequencing using various single-case experimental designs. Participants ( N = 21) were generally preschool-aged children (mean age = 5.7 years) diagnosed with autism spectrum disorder (ASD; n = 9) or other developmental disabilities ( n = 12). Subsequent analysis of articles that met quality indicators of the What Works Clearinghouse ( n = 12) suggests that research does not support the effectiveness of the procedure for increasing food acceptance. Implications for practice and future studies involving high-probability sequencing follow a discussion of findings.